Digital Transformation for the Future of Education: Community Service in Website Design Company Profile Tutoring Institution Scholastica Education Center (SEC) - Putri Prasetyaningrum; Scholastica Larissa Zafira Lewoema (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This community service project explores the growing and crucial role of tutoring institutions (Bimbel) in providing important academic support to students in need. Traditionally, tutoring has been conducted in physical settings, involving face-to-face interactions between students and teachers. However, with the rapid advancement of technology and the soaring popularity of the internet, online tutoring has witnessed a tremendous surge in demand, becoming easily accessible and highly sought after. The Scholastica Education Center (SEC) located in Larantuka, East Flores, NTT, recognizes the importance of following technological advances and using them to increase access to education for children throughout Indonesia. Through these community service initiatives, SEC is wholeheartedly dedicated to making the most impactful contribution to the education sector, catering to the diverse needs and academic levels of its students. An integral aspect of promoting online learning programs is the role of official websites. As a result, Servants designed and launched a company profile website for the SEC, leveraging cutting-edge web technologies such as HTML, CSS, and Javascript. The implementation of this website aims to increase SEC's reach to its target audience, effectively disseminate information about their online tutoring services and programs, and provide an interactive and enriching learning experience for all students. The overall goal of this community service project is to generate a positive and transformative impact by improving the overall quality of education in Indonesia. The seamless integration of technology and the ease of access to learning through online tutoring offered by leading institutions such as the Scholastica Education Center actively contribute to the educational progress and holistic success of students.